A szakoktatás reformjának menedzsment szempontú megközelítése - Láczay, Magdolna (Közép-Európai Közlemények, 2016)
Reaching, measuring and improving effectiveness have been in focus of many scholars and practitioners of economics since the beginnings of commodity production. Human factors were not considered so early. Some find it degrading to regard humans as part of capital while others find that investment in people (education and development) creates valuable resource for organizations. This debate is present in many disciplines in both the oretical and practical economics including economical sociology, education and management studies. Quality enhancement of human resources is the object of different types of educational cooperation, developmental concepts that target readily usable competencies and outstanding outcomes from the talent pool. Talent, however is a scarce resource hence in the age of knowledge-based economy there is competition for talents. The meaning of “talent” has expanded to include high-qualified, multicompetent versatile workforce. There is a growing demand for such people and the economy as well as the society expects education to produce them.Hungarian economy follows the global trend but the status of underprivileged groups and particularly the Roma communities make a serious diversion from these trends.